Branched methoxydiphenylamine-substituted fluorene derivatives as hole transporting materials for high-performance perovskite solar cells. Issue 5 (20th April 2016) - Malinauskas, Tadas; Saliba, Michael; Matsui, Taisuke; Daskeviciene, Maryte; Urnikaite, Simona; Gratia, Paul; Send, Robert; Wonneberger, Henrike; Bruder, Ingmar; Graetzel, Michael; Getautis, Vytautas; Nazeeruddin, Mohammad Khaja
Abstract : Small-molecule fluorene HTMs were synthesized and tested in perovskite solar cell, PCE of up to 19.96% was reached. Abstract : Small-molecule hole transporting materials based on methoxydiphenylamine-substituted fluorene fragments were synthesized and incorporated into a perovskite solar cell, which displayed a power conversion efficiency of up to 19.96%, one of the highest conversion efficiencies reported. The investigated hole transporting materials were synthesized in two steps from commercially available and relatively inexpensive starting reagents, resulting in up to fivefold cost reduction of the final product compared with spiro-OMeTAD. Electro-optical and thermoanalytical measurements such as UV/Vis, thin-film conductivity, hole mobility, DSC, TGA, ionization potential and current voltage scans of the full perovskite solar cells have been carried out to characterize the new materials.